2022
DOI: 10.3390/jmse10010096
|View full text |Cite
|
Sign up to set email alerts
|

Review of Top-Down Method to Determine Atmospheric Emissions in Port. Case of Study: Port of Veracruz, Mexico

Abstract: Indicators of environmental policies in force in Mexico, fossil fuels will continue to be used in industrial sectors, especially marine fuels, such as marine diesel oil, in port systems for some time. Considering this, we have evaluated several methods corresponding to a top-down system for determining fuel consumption and sulfur dioxide atmospheric emissions for the port of Veracruz in 2020 by type of ship on a daily resolution, considering a sulfur content of 0.5% mass by mass in marine fuel. After analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…Despite this, due to the nature of most of the reported ports and the dimensions of the ports, it can be stated that in general, the container-type vessels were the ones that generated a higher level of emissions. Other studies showed that container vessels had higher fuel usage, whereas tanker vessels had higher ambient pollution levels in the berthing position, and that the primary discrepancies are related to the load factor parameter, the ME and AE power, and fuel consumption by vessel type [24].…”
Section: Literature Review and Problem Statementmentioning
confidence: 96%
See 2 more Smart Citations
“…Despite this, due to the nature of most of the reported ports and the dimensions of the ports, it can be stated that in general, the container-type vessels were the ones that generated a higher level of emissions. Other studies showed that container vessels had higher fuel usage, whereas tanker vessels had higher ambient pollution levels in the berthing position, and that the primary discrepancies are related to the load factor parameter, the ME and AE power, and fuel consumption by vessel type [24].…”
Section: Literature Review and Problem Statementmentioning
confidence: 96%
“…Ship emission inventories can be classified into two primary methods: fuel-based (topdown) and activity-based (bottom-up) approaches. The fuel-based methodology relies on the combination of marine fuel sales data, encompassing quantities and types of fuel, along with fuel-related emission factors [24,27]. Several countries utilize the fuel-based approach (top-down) to develop national and international emission inventories.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico, recent studies [48][49][50] represent a starting point for the elaboration and updating of Atmospheric Emissions Inventories for maritime activity. They considered two traditional methods of identifying the atmospheric emission levels of the main pollutants and greenhouse gases (GHG) produced during the combustion process of different ship types.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, plenty of works deals with the assessment of port emissions related to a specific aspect [9,10] or a specific port [11,12]. However, works focusing on both maritime and terrestrial emissions in a wide geographical area based on a common methodology are still missing.…”
Section: Introductionmentioning
confidence: 99%